Diffuse, persistent milia in two infants. - Menni, S.; Piccinno, R. (European Journal of Pediatric Dermatology, 2018)
The Authors describe two unusual cases of diffuse, persistent milia, appeared after the first month of life. Histopathology revealed an intradermal small cyst lined by flattened epidermal cells. The Authors differentiate the two cases from other milia in infants. The father of one of the two children was affected by sebocystomatosis. Such association in the same family has never been reportcd in the literature.